The epidemiology of SARS-CoV-2, Influenza, and Respiratory Syncytial Virus circulation among adult patients with acute respiratory illness in Kampala Metropolitan Area in Uganda - James Arinaitwe; Barnabas Bakamutumaho; Levicatus Mugenyi; Noah Kiwanuka; Patricia Alupo; Aida N. Kawuma; Karen Ndahura; Maria Sekimpi; Eva Akurut; Winters Muttamba; Moses Joloba; Moses Ocan; et al. (PLoS ONE, 2026)
Background Acute respiratory infections (ARI) caused by viruses such as SARS-CoV-2, influenza, and respiratory syncytial virus (RSV) posed significant public health challenges, particularly in low-income countries. Understanding the co-circulation dynamics of these pathogens is crucial for effective public health monitoring, surveillance, and control interventions. This study aimed to characterize the epidemiology of SARS-CoV-2, influenza, and RSV co-circulation among patients with ARI in Uganda’s central business districts. Methods A retrospective cohort study was conducted among 1,265 adult outpatients aged 18 years and older presenting with ARI in Kampala, Wakiso, and Mukono districts. Data were collected for the period from March 2023 through April 2024. Nasopharyngeal swabs were collected and tested for SARS-CoV-2, influenza A/B, and RSV using RT-PCR. Data on demographics, clinical presentation, and SARS-CoV-2 vaccination status were analyzed using descriptive statistics and time series analysis. Results RSV was the most prevalent pathogen (5.5%), followed by SARS-CoV-2 (5.1%), Influenza A (4.4%), and Influenza B (1.7%). Individuals aged 45 and older were more likely to test positive for SARS-CoV-2. There was a significant difference in pathogen presence by occupation (p = 0.03), with health workers showing the highest prevalence of SARS-CoV-2 infection, while prevalence did not differ significantly by sex. Seasonal trends showed bimodal peaks for SARS-CoV-2, influenza A, and RSV, with the highest frequency observed between April 2023 to June 2023 and November 2023 to February 2024. However, Influenza B exhibited a single prolonged peak. SARS-CoV-2 vaccination was associated with a higher prevalence of SARS-CoV-2 (8.7% vs. 2.8%, p = 0.023) but not with influenza or RSV prevalence. Conclusion The co-circulation of SARS-CoV-2, influenza, and RSV highlights Uganda’s ongoing respiratory virus burden. Seasonal patterns and recurrent outbreaks underscore the need for sustained surveillance, targeted vaccination, and public health interventions to mitigate the impact of these pathogens, particularly in vulnerable populations.